FM0807 decelerates experimental arthritis progression by inhibiting inflammatory responses and joint destruction via modulating NF-κB and MAPK pathways. Issue 9 (3rd September 2019) - Zhang, Nanwen; Liu, Zhiwei; Luo, Hongbin; Wu, Weifang; Nie, Kaimei; Cai, Lin; Tan, Shuangyu; Chen, Xiaole; Huang, Ying; Liu, Jiaxing; Lv, Meina; Zhang, Xin; et al.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic articular synovial inflammatory disease. The precise etiology underlying the pathogenesis of RA remains unknown. We aimed to investigate the inhibitory effect of curcumin analog FM0807 (curcumin salicylate monoester, 2-hydroxy-, 4-[(1E, 6E)-7-(4-hydroxy-3-methoxyphenyl)-3, 5-dioxo-1, 6-heptadien-1-yl]-2-methoxyphenyl ester) on experimental RA and investigate its possible mechanisms of action. Method: Rats with Freund's complete adjuvant (FCA)-induced arthritis (AIA) were administered aspirin (0.1 mmol.kg −1 ), curcumin (0.1 mmol.kg −1 ), FM0807 (0.1, 0.2 mmol.kg −1 ) and vehicle via gastric gavage, from days 7 to 21, once daily. The hind paw volume and arthritis index (AI) were measured, and radiographic and histological examinations were performed. Twenty-one days later, the animals were killed and left ankle joints were removed to measure protein expression of the elements of the nuclear factor κB (NF-κB) and mitogen-activated protein kinase (MAPK) pathway by Western blot analysis. The enzyme-linked immunosorbent assay (ELISA) was employed to measure synovial fluid levels of tumor necrosis factor-α (TNF-α), interleukin (IL)-6, IL-1β and IL-10. Results: Compared with AIA group, FM0807 reduced the AI and swelling of the injected hind paw in a dose-dependent manner, and inhibited increases in inflammatory cell infiltration, pannus formation and cartilage destruction. FM0807 also potently attenuated the increase in the expression of inflammatory factors TNF-α, IL-6 and IL-1β in synovial fluid, while IL-10 levels were also elevated. FM0807 significantly suppressed phosphorylation of extracellular-signal-regulated kinase (ERK) 1/2 (ERK1/2), c-Jun-N-terminal kinase (JNK) 1/2 (JNK1/2), p38MAPK, inhibitor of NF-κB kinase (IKK), IκB and NF-κB p65 protein, (all P <0.05), which displayed more potential effects compared with those of the aspirin and curcumin groups. Conclusion: FM0807 exerts its therapeutic effects on RA by inhibiting cartilage degeneration. FM0807 treatment might be an effective therapeutic approach for RA.